ANALISIS KONTRIBUSI REALISASI PENDAPATAN ASLI DAERAH TERHADAP REALISASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH KABUPATEN KEBUMEN TAHUN 2011-2014 - Eko Darmawan Suwandi (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2016)
Anggaran Pendapatan dan Belanja Daerah (APBD) is a local government's annual financial plan. At the end of the period of government financial reports one Realized Budget Report in which there is a realization of Pendapatan Asli Daerah (PAD). PAD is a component of Pajak Daerah, Retribusi Daerah, Hasil Kekayaan Yang Dipisahkan, and Lain-lain PAD yang Sah. The objective of this study was to determine the contribution of PAD Realization to Realization of the APBD, the contribution Realization components PAD to PAD Realization and the degree of local financial independence Kebumen seen from the comparison between the PAD Realization to Actual Funds Transfer. The analysis used in this study is an analysis of the contribution to the PAD Realization Kebumen Realization APBD, contributions Realization components PAD to Realization Kebumen, and Regional Financial Independence Ratio Kebumen Contributions Realization of the PAD. The results showed that the contribution of Realization PAD to Realization APBD of Kebumen district in 2011-2014 experienced a positive increase by an average of 8.31%. The ability of financial independence Kebumen of the Contributions Realization PAD still in the low category once the level of the average ratio of 9.56%. This suggests that the ability of the financial independence of the Kebumen Regency Contributions Realization of PAD is not optimal so we need more leverage in exploring and managing its resource potential. Keywords: APBD, LRA, PAD, contributions, self-sufficiency ratio.